2019
DOI: 10.3390/app9030399
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Optical Networks Based on CDC-ROADM Technology

Abstract: New generation of optical nodes in dense wavelength division multiplexed networks enables operators to improve service flexibility and make significant savings, both in operational and capital expenditures. Thus the main objective of the study is to minimize optical node resources, such as transponders, multiplexers and wavelength selective switches, needed to provide and maintain high quality dense wavelength division multiplexed network services using new generation of optical nodes. A model based on integer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Hence, smaller calculation time is of clear benefit. Secondly, it was observed that the calculation time of standard optimization methods (e.g., ILP) growths rapidly with the number of network nodes [7]. Thus, for large networks, application of heuristic methods becomes indispensable.…”
Section: Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, smaller calculation time is of clear benefit. Secondly, it was observed that the calculation time of standard optimization methods (e.g., ILP) growths rapidly with the number of network nodes [7]. Thus, for large networks, application of heuristic methods becomes indispensable.…”
Section: Problem Formulationmentioning
confidence: 99%
“…However, the IP optimization results show that even if the IP approach is applicable, it is inefficient for larger networks since the design task is, in general, NP-complete [3]. The numerical efficiency limitations are particularly acute in the context of routing and wavelength assignment (RWA) [4][5][6] and routing and spectrum allocation (RSA) [7][8][9][10] problems, which are at the heart of DWDM network optimization. Moreover, the constraints and cost functions are in a general case nonlinear and thus may further complicate the situation.…”
Section: Introductionmentioning
confidence: 99%
“…It offers a flexible and multiplexed optical network infrastructure and on-demand guaranteed time-shared multi-granular services. This solution is a contentionless [5] solution through the deployment of a central resource allocation engine of route, wavelength, and time assignment, in charge of setting up the sub-wavelength paths.…”
Section: Evolution Stage 1: Tson Baselinementioning
confidence: 99%
“…SDN uses a logically centralized control plane in a DWDM network that is realized using purpose-built flexible hardware such as reconfigurable optical add/drop multiplexers (ROADMs), flexible line interfaces, etc. [7,8]. In modern DWDM optical networks, following the software defined network paradigm, DWDM network reconfiguration is becoming more frequent, making the evolving network more resilient and adapting faster to real changes in bandwidth demand so that network reconfigurations can closely match changes in bandwidth demand.…”
Section: Introductionmentioning
confidence: 99%